Assessment of Climate Change Effects on the Hydrological Regime of Bagmati River Basin using SWAT Model - Shrestha, Smriti; Maskey, Gunjan; Kayastha, Rijan Bhakta (Journal of Hydrology and Meteorology, 2023)
Developing economies have been particularly vulnerable to the consequences of climate change due to their quickly growing populations and underdeveloped social and economic infrastructure. The Bagmati River Basin (BRB) belonging to such an economy is susceptible to the effects of climate change, including droughts and floods brought upon by changes in discharge. This study assessed the potential effects of climate change on discharge in BRB using the Soil and Water Assessment Tool (SWAT). The model was calibrated and validated based on observed flow data from 2000-2010 at two outlets: Khokana and Padhera Dovan. Using R2, NSE, PBIAS, RSR, and p-factor, the goodness of fit between the final simulated values and the observed values were evaluated. Historical data from three meteorological stations and bias-corrected global climate model (GCM) outputs from the ACCESS-CM2 model were used to drive the calibrated SWAT model under two scenarios (SSP 2-4.5 and SSP 5-8.5) from the IPCC Sixth Assessment Report (AR6). The study demonstrated long-term spatial and temporal variations in hydrologic responses to future climate changes, providing insights for water resources managers and those involved in mitigating natural hazards in the region.